Prefabrication of vascularized bone graft using an interconnected porous calcium hydroxyapatite ceramic in presence of vascular endothelial growth factor and bone marrow mesenchymal stem cells: Experimental study in rats - Sever, Celalettin (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: The purpose of this experimental pilot study was to create a prefabricated vascularized bone graft using interconnected porous calcium hydroxyapatite ceramic (PCHC) block by combining vascular bundle implantation, rat bone marrow mesenchymal stem cells and administration of vascular endothelial growth factor (VEGF) in a rat model. MATERIALS AND METHODS: Sixty male Sprague-Dawley rats were used. Experimental animals were divided into six groups, each of which comprised 10 rats. The PCHC blocks were implanted in the medial thigh region in groups I, III, and V without vascular bundle implantation. The PCHC blocks were vascularized by the superficial inferior epigastric artery and vein in groups II, IV and VI. These vessels were passed through the hole of the PCHC blocks. Mesenchymal stem cells were administered into the PCHC in groups III, IV, V and VI. In addition, both mesenchymal stem cells and VEGF were administered in group V and VI. The presence and density of any new bone formation and neovascularization from the vascular bundle was evaluated by X-ray, microangiography, scintigraphy, biochemical analysis and histomorphometry. RESULTS: The newly formed vessels and bone formations were significantly greater in group VI, in which both mesenchymal stem cells and VEGF were applied. CONCLUSION: This preliminary study suggests that: Both mesenchymal stem cells and VEGF provide vascularized bone prefabrication by enhancing neovascularization and osteogenesis in a shorter time compared to only VEGF application.